Boosting CO2-to-CO conversion on a robust single-atom copper decorated carbon catalyst by enhancing intermediate binding strength. Issue 3 (4th January 2021) - Chen, Shixia; Li, Yuewei; Bu, Zhuogang; Yang, Fangqi; Luo, Junhui; An, Qizheng; Zeng, Zheling; Wang, Jun; Deng, Shuguang
Abstract : The hydrogen-bond strengthen the *COOH adsorption and lower the CO2 (g)→*COOH energy barrier on Cu–N–C electrocatalyst, simultaneously yielding a high CO FE and TOF. Abstract : The ability to manipulate the binding strengths of intermediates on a catalyst is extremely challenging but essential for active and selective CO2 electroreduction (CO2 RR). Single-atom copper anchored on a nitrogenated carbon (Cu–N–C) structure is still rarely unexplored for efficient CO production. Herein, we demonstrate a plausible hydrogen-bonding promoted strategy that significantly enhances the *COOH adsorption and facilitates the *CO desorption on a Cu–N–C catalyst. The as-prepared Cu–N–C catalyst with Cu–N3 coordination achieves a high CO faradaic efficiency (FE) of 98% at −0.67 V ( vs. reversible hydrogen electrode) as well as superior stability (FE remains above 90% over 20 h). Notably, in a three-phase flow cell configuration, a remarkable CO2 to CO FE of 99% at −0.67 V accompanying a large CO partial current density of 131.1 mA cm −2 at −1.17 V was observed. Density functional theory calculations reveal that the Cu–N3 coordination is potentially stabilized by an extended carbon plane with six nitrogen vacancies, while three unoccupied N sites are spontaneously saturated by protons during the CO2 RR. Therefore, the hydrogen bonds formed between the adsorbed *COOH and adjacent protons significantly reduce the energy barrier of *COOH formation. After the first proton-coupled electron transfer process, the adsorbed *CO species are easily released to boost the CO production.